Studies on nutrient export and extent of nutrient recycling in coconut based high density multispecies cropping system - P. Subramanian; D.V. Srinivasa Reddy; C. Palaniswami; P. Gopalasundaram; A.K. Upadhyay (International Coconut Community, 2005)
Investigations were carried out to assess the biomass available for recycling from coconut based high density multispecies cropping system (coconut, clove, banana and pineapple) under graded levels of fertilizers (full, two-third, one-third, one-fourth and one-fifth of the recommended level of fertilizer for each of the component crops and control). The total biomass removed from the system ranged from 19.1 to 27.6 t ha-1 year-1. The highest biomass production was recorded from two-third level of fertilizer dose (27.6 t ha-1 year-1). Out of the total biomass obtained, the quantity available for recycling ranged from 12.7 to 18.5 t ha-1 year-1, which can contribute 56 to 110 kg N, 6.7 to 13.5 kg P and 108 to 225 kg K per hectare.